Caspase inhibitors: a review of recently patented compounds (2013-2015). (2nd January 2018) - Lee, Hyemin; Shin, Eun Ah; Lee, Jae Hee; Ahn, Deoksoo; Kim, Chang Geun; Kim, Ju-Ha; Kim, Sung-Hoon
ABSTRACT: Introduction : Although many caspase inhibitors have been patented, caspase inhibitors have not entered the market due to their toxicity and poor pharmacokinetic profile. Areas covered : In this article, we review patents (2013–2015) for peptide and non-peptide caspase inhibitors and their compositions. Expert opinion : Noteworthy patents include a peptidic caspase-2 inhibitor for nasal administration and a peptidomimetic caspase-6 inhibitor that can be administered via several routes for the treatment of neurodegenerative diseases. Furthermore, caspase-1 inhibitors for contact dermatitis and inflammation, cardiovascular diseases, and liver diseases and a caspase-3 inhibitor for cerebral stroke have been patented. Of particular interest is the novel use of tyrosine kinase inhibitors (sunitinib and its derivatives) for the prevention and treatment of age-related ocular diseases via inhibition of the caspase-3, dual-leucine zipper kinase (DLK) and leucine zipper-bearing kinase (LZK) pathways. However, for effective clinical application of caspase inhibitors, novel peptidic and nonpeptidic caspase inhibitors with lower toxicity and improved efficacy should be developed via structural modifications, and further animal studies and preclinical and clinical trials are needed. In addition, the poor pharmacokinetic properties of classic caspase inhibitors may be improved by using advanced drug delivery systems that employ liposomes, polymers, and nanoparticles through effective administration routes.